2008
DOI: 10.1111/j.1365-2958.2008.06227.x
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic assembly of chemoreceptor clusters in Escherichia coli

Abstract: SummaryChemoreceptors and cytoplasmic chemotaxis proteins in Escherichia coli form clusters that play a key role in signal processing. These clusters localize at cell poles and at specific positions along the cell body which correspond to future division sites, but the details of cluster formation and the mechanism of cluster distribution remain unclear. Here, we used fluorescence microscopy to investigate how the numbers and sizes of receptor clusters depend on the expression level of chemotaxis proteins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 39 publications
2
79
0
Order By: Relevance
“…Recent reports have suggested that these clusters are formed by stochastic self-assembly, which yields a somewhat regular distribution of clusters along the cell length (Thiem and Sourjik 2008). This distribution is similar to the positioning of E. coli's peritrichous flagella and is believed to facilitate a rapid response to chemotactic stimuli because the diffusion time of phosphorylated CheY to a flagellar motor is minimized (Sourjik and Berg 2002;Lipkow et al 2005).…”
mentioning
confidence: 77%
“…Recent reports have suggested that these clusters are formed by stochastic self-assembly, which yields a somewhat regular distribution of clusters along the cell length (Thiem and Sourjik 2008). This distribution is similar to the positioning of E. coli's peritrichous flagella and is believed to facilitate a rapid response to chemotactic stimuli because the diffusion time of phosphorylated CheY to a flagellar motor is minimized (Sourjik and Berg 2002;Lipkow et al 2005).…”
mentioning
confidence: 77%
“…MCPs likely are inserted at random sites throughout the cell membrane and then are subject to diffusion-mediated clustering that results in the recruitment of additional chemotaxis proteins (6,9,(33)(34)(35)(36). Because V. parahaemolyticus chemotaxis proteins form randomly localized clusters in the absence of ParC and ParP, it is likely that such a diffusion-mediated mechanism also contributes to the assembly of the V. parahaemolyticus chemotactic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the cytoplasmic signaling domains of the receptors are sufficient for the formation of receptor arrays (6), although the formation is enhanced in the presence of CheW or CheA (6)(7)(8). Recent studies have suggested that array formation in Escherichia coli is a stochastic process in which individual receptors are inserted randomly in the membrane, where they diffuse freely and either join existing arrays or nucleate new ones (9). This process results in a nonuniform distribution of signaling arrays at cell poles and randomly along the cell length (10).…”
mentioning
confidence: 99%
“…Chemoreceptor clusters are predominantly polar (Maddock and Shapiro, 1993), but a few are regularly positioned along the cell body (Sourjik and Armitage, 2010). This periodic arrangement is spontaneous: chemoreceptors stochastically self-assemble in a concentration-dependent manner to build new clusters or to expand old ones, and the formation of new clusters is entropically favored far away from pre-existing ones (Thiem et al, 2007;Thiem and Sourjik, 2008;Wang et al, 2008;Greenfield et al, 2009). As a consequence of this organization, larger clusters appear confined to future division sites (Thiem et al, 2007).…”
Section: Growth-dependent Transmission From the Sidewallmentioning
confidence: 99%